Apolipoprotein A-I increases the activity of lysosomal glycosidases in the liver of mice with BCG-induced tuberculosis inflammation - L. M. Polyakov; R. A. Knyasev; M. V. Kotova; G. S. Russkikh; E. I. Soloveva; A. V. Ryabchenko (Сибирский научный медицинский журнал, 2021)
This work shows the ability of apolipoprotein A-I to influence the activity of lysosomal glycosidases in the liver of mice in a model of BCG-induced tuberculous inflammation. The aim of the investigation was to study the activity of lysosomal glycosidases in the liver of mice using a model of BCG-induced tuberculous inflammation after intravenous administration of apolipoprotein A-I. Material and methods. The studies were performed on male CBA mice weighing 20-22 g. Disseminated tuberculous inflammation was modeled by a single intraperitoneal injection of 0.5 mg of BCG vaccine. The activity of lysosomal glycosidases was assessed spectrofluorimetrically by the content of hydrolysis products of the corresponding fluorogenic substrates. Results. Tuberculous inflammation led to a pronounced decrease in the activity of lysosomal glycosidases in the liver. Thus, β-galactosidase was decreased 2.3 times, β-glucosidase – 2.8 times, β-glucuronidase – 2.5 times compared with healthy animals. Intravenous injection of apolipoprotein A-I to animals against the background of BCG infection prevented a significant decrease in the enzymatic activity of glycosidases and these values practically did not differ from the control values. Conclusions. Enzymatic activity of lysosomal glycosidases in the group of mice with intravenous administration of apolipoprotein A-I against the background of BCG infection was 1.5–2 times higher than the corresponding indicators in the group of animals with BCG-infection without administration of apolipoprotein A-I, i.e. without treatment.